Modelling and Parameters Identification of a Quadrotor Using a Custom Test Rig - Mohammad Shafiq Mohammad Ashraf; Mohamad Shukri Zainal Abidin; Mohd Saiful Azimi Mahmud; Muhammad Khairie Idham Abd Rahman; Zakarya Mohammed Nasser Saleh Motea (Institute of Advanced Engineering and Science, 2018)
Quadrotor by nature is a very unstable system and flying it without any feedback control algorithm is deemed impossible. However, before designing the control system, system identification need to be conducted as the accuracy of the control system depends highly on the accuracy of the model. Therefore, this paper explained the design of the quadrotor model with an “X” configuration using the Euler-Newton model. Two types of test rig were designed to measure the thrust coefficient, torque coefficient and throttle command relation parameter needed in the model. Other parameter such as moment of inertia was also being measured by separating the quad rotor model into several sections: Motors, Electronics Speed Controllers (ESC) and Central Hub. All parameters needed in the designed quad rotor model has been successfully identified by measuring the parameters using the custom-built quad rotor and test rigs. The parameters found in this paper will be used in designing the control system for the quadrotor.